2006
DOI: 10.2174/138527206778521268
|View full text |Cite
|
Sign up to set email alerts
|

Current Progress in the Acetate/Methyl Ketone Aldol Reaction

Abstract: The aldol reaction of acetate and methyl ketone-based donors with aldehyde acceptors is reviewed. Emphasis is placed on major advances reported in the last 10-15 years. Several methods for inducing chirality at the newly formed stereogenic center are discussed, including popular alternate methods for equivalent syntheses. Different methods for stereospecific synthesis are compared in terms of yield, selectivity, ease of synthesis, and applicability to both small molecule and large macrolide production. + Aldol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…[10][11][12][13] Since CILs used as catalyst in aldol reaction by Luo et al 14 in 2007, many CILs were developed as catalysts for asymmetric reactions. However, in asymmetric reactions where CILs cannot be applied as catalysts, using CILs as the solvent to investigate the chiral inducing capabilities has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Since CILs used as catalyst in aldol reaction by Luo et al 14 in 2007, many CILs were developed as catalysts for asymmetric reactions. However, in asymmetric reactions where CILs cannot be applied as catalysts, using CILs as the solvent to investigate the chiral inducing capabilities has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations revealed that the orientation of the reaction is in close relationship with the composition of the reactants and the experimental condition. In most cases, this type of reaction could provides an ,-unsaturated ketone via aldol condensation (the Claisen-Schmidt condensation) [1][2][3][4][5][6][7][8] or a -hydroxyketone via direct aldol addition [9][10][11][12][13] (Scheme 1). The reaction could also produces linear 1,5-diones [14][15][16], triones [17], or cyclohexane derivatives [18][19][20][21][22] via the multimolecular reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Many protocols have been established in which specially designed catalysts achieve excellent yields and selectivities [10][11][12]. Proline and proline derivatives were found as the most promising catalysts for aldol reactions [13,14].…”
Section: Introductionmentioning
confidence: 99%